Does personality affect premating isolation between locally-adapted populations?. Issue 1 (December 2016) - Sommer-Trembo, Carolin; Bierbach, David; Arias-Rodriguez, Lenin; Verel, Yesim; Jourdan, Jonas; Zimmer, Claudia; Riesch, Rüdiger; Streit, Bruno; Plath, Martin
Abstract Background One aspect of premating isolation between diverging, locally-adapted population pairs is female mate choice for resident over alien male phenotypes. Mating preferences often show considerable individual variation, and whether or not certain individuals are more likely to contribute to population interbreeding remains to be studied. In thePoecilia mexicana -species complex different ecotypes have adapted to hydrogen sulfide (H2 S)-toxic springs, and females from adjacent non-sulfidic habitats prefer resident over sulfide-adapted males. We asked if consistent individual differences in behavioral tendencies (animal personality) predict the strength and direction of the mate choice component of premating isolation in this system. Results We characterized focal females for their personality and found behavioral measures of 'novel object exploration', 'boldness' and 'activity in an unknown area' to be highly repeatable. Furthermore, the interaction term between our measures of exploration and boldness affected focal females' strength of preference (SOP) for the resident male phenotype in dichotomous association preference tests. High exploration tendencies were coupled with stronger SOPs for resident over alien mating partners in bold, but not shy, females. Shy and/or little explorative females had an increased likelihood of preferring the non-resident phenotype and thus, are more likely to contribute to rare population hybridization. When we offered large vs. small conspecific stimulus males instead, less explorative females showed stronger preferences for large male body size. However, this effect disappeared when the size difference between the stimulus males was small. Conclusions Our results suggest that personality affects female mate choice in a very nuanced fashion. Hence, population differences in the distribution of personality types could be facilitating or impeding reproductive isolation between diverging populations depending on the study system and the male trait(s) upon which females base their mating decisions, respectively.